2011
DOI: 10.1093/infdis/jir592
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant BCG ΔureC hly+ Induces Superior Protection Over Parental BCG by Stimulating a Balanced Combination of Type 1 and Type 17 Cytokine Responses

Abstract: Background. New vaccines against tuberculosis (TB) are urgently needed because the only available vaccine, Mycobacterium bovis bacillus Calmette-Guérin (BCG), fails to protect against pulmonary TB in adults. The recombinant ΔureC hly+ BCG (rBCG) is more efficient than parental BCG (pBCG) against pulmonary TB in preclinical studies and has proven safe and immunogenic in phase I clinical trials.Methods. In an attempt to identify the mechanisms underlying the superior protection of rBCG, we compared the immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 40 publications
2
110
2
2
Order By: Relevance
“…At least eight distinct cytokine-producing populations of M72-specific CD4 T-cell responses were induced and persisted to at least 7 months after the first vaccination, including a discrete population of Th17 cells. Studies in mice have suggested Th17 cells play an active role in production of chemokines that recruit IFN-g-producing CD4 T cells to the lungs to restrict mycobacterial growth after challenge (16), and may be an important component of long-term control of Mtb infection (17). Moreover, polyfunctional CD4 T cells simultaneously producing IFN-g, TNF-a, and IL-2 in the lung have been correlated with better protection against Mtb challenge in mice (18).…”
Section: Discussionmentioning
confidence: 99%
“…At least eight distinct cytokine-producing populations of M72-specific CD4 T-cell responses were induced and persisted to at least 7 months after the first vaccination, including a discrete population of Th17 cells. Studies in mice have suggested Th17 cells play an active role in production of chemokines that recruit IFN-g-producing CD4 T cells to the lungs to restrict mycobacterial growth after challenge (16), and may be an important component of long-term control of Mtb infection (17). Moreover, polyfunctional CD4 T cells simultaneously producing IFN-g, TNF-a, and IL-2 in the lung have been correlated with better protection against Mtb challenge in mice (18).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 The exogenous listeriolysin facilitates the perforation of the phagosome membrane, allowing the release of recombinant BCG antigens into the cytosol of host cells. 35 Hence, the vaccine is able to stimulate the CD8 T cells via major histocompatibility complex (MHC) I presentation, and further activate both T helper (Th)1 and Th17 cytokine responses. 35,36 In addition, an endogenous gene ureC, encoding urease C, has been deleted in VPM1002.…”
Section: Vpm1002mentioning
confidence: 99%
“…35 Hence, the vaccine is able to stimulate the CD8 T cells via major histocompatibility complex (MHC) I presentation, and further activate both T helper (Th)1 and Th17 cytokine responses. 35,36 In addition, an endogenous gene ureC, encoding urease C, has been deleted in VPM1002. 35 Urease C is crucial for the hydrolysis of urea, resulting in the ammonia production and a basic environment in the milieu.…”
Section: Vpm1002mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the characteristics of ␦2 CDR3 from ␥␦ T cells of TB patients may identify the predominant CDR3 and the sequence that specifically reacts with TB. Furthermore, ␣␤ T cells identify peptide or protein antigens that are related to M. tuberculosis (11)(12)(13)(14)(15), but little is known about the antigens recognized by ␥␦ T cells, except for various phosphoantigens. These phosphoantigens may not inhibit intracellular mycobacterial growth (16).…”
mentioning
confidence: 99%